Using the TAM Model to Predict Undergraduate Distance Learners Behavioural Intention to Use the Makerere University Learning Management System - Kasula Munabi, Susan; Aguti, Jessica; Mutambo Nabushawo, Harriet (Open Access Library Journal, 2020)
The purpose of the research was to predict the factors that affect the undergraduate distance learners behavioural intention to use the Makerere University E-learning Environment (MUELE) at Makerere university using the Learning Management System-Technology Acceptance Model (LMS-TAM). The LMS-TAM used for this study, was made up of the three factors from original Technology Acceptance Model (TAM): perceived ease of use, perceived usefulness, and behavioural intention including an external factor called enjoyment. It involved distribution of self-administered validated questionnaires to 114 students. A Partial least squares structural equation modeling approach was used to analyse the data captured by the study questionnaire. The model predicted that enjoyment and perceived usefulness were the factors that influenced learners’ continued use of the LMS. These findings were significant with enjoyment having a greater effect (0.85) on behavioural intention than perceived usefulness with an effect of (0.40). This information can be utilised in the design of interventions that increase learners’ use of the learning management system.
Keywords: Learning Management System-Technology Acceptance Model; LMS-TAM; Structural Equation Modeling; Distance learners